2018
DOI: 10.1186/s13048-018-0435-7
|View full text |Cite
|
Sign up to set email alerts
|

Is the ovarian reserve influenced by vitamin D deficiency and the dress code in an infertile Iranian population?

Abstract: BackgroundIn the recent years, vitamin D has become a topical subject and a focus of research not only in reproductive medicine but across many medical disciplines. In reproductive medicine, studies have identified an association between vitamin D status in women and ovarian reserve. In humans, exposure of the skin to sunlight is the main important source of vitamin D. A dress code of wearing concealing clothing is a risk factor for vitamin D deficiency. The objective of this prospective observational study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…The current study results are in the line with those of other studies, who could not find a definite correlation between vit D level and AFC [5]- [7]. On the contrary, our results contrast with the literature reports that have found a negative correlation between vit D and AFC [8].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The current study results are in the line with those of other studies, who could not find a definite correlation between vit D level and AFC [5]- [7]. On the contrary, our results contrast with the literature reports that have found a negative correlation between vit D and AFC [8].…”
Section: Discussionsupporting
confidence: 83%
“…In comparison with the study of Arefi et al, [8] which aimed to evaluate the vitamin D status in an infertile population in Iran and to correlate vitamin D concentrations with parameters such as female age, skin type, degree of skin concealment and antral follicle count (AFC) as parameter of the ovarian reserve, and reported that total of 189 patients have been included in this prospective observational study, the mean age of the study group was 32.21 years, and the mean BMI of the patients was 26.70 kg/m 2 with a range of 17.9-35.5 kg/m 2 .The mean vit D was for study group was 15.46 ng/ml and while the mean AFC in all patients was 10.84 follicle . There was negative correlation between vit D level and AFC in the study group .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…For example, kiwifruit, nuts, tomatoes are rich in vitamins C, D, and E; walnuts, peanuts, cherries, corn are high in melatonin. A prospective study showed that there is a highly significant correlation between vitamin D deficiency and DOR ( Arefi et al, 2018 ). The combined use of vitamin E and C can prevent apoptosis of ovarian tissue following mancozeb exposure in the first generation of mouse pups ( Mahdi et al, 2019 ).…”
Section: Natural Antioxidant-based Interventions To Reduce Oxidative mentioning
confidence: 99%
“…However, it can be assumed that most patients in those studies were not expected to be subjected to concealing dress due to their sociocultural backgrounds. In contrast to these study findings, the study of Arefi et al [31] was conducted in a society in which women wear concealing clothing and this dress-code is imposed from an early age. In this study, women diagnosed as severely vitamin D-deficient demonstrated a clear correlation between vitamin D deficiency and a reduced ovarian reserve.…”
Section: Differences Observed In Vitamin D Deficiency Rates Betweenmentioning
confidence: 72%